Panorama y perspectivas de la horticultura nacional - Kirschbaum, Daniel Santiago; Barón, Claudio; Aquindo, Natalia Soledad; Bedogni, Maria Cecilia (Asociación Argentina de Horticultura (ASAHo), 2024)
Ponencia y poster